Making Career Stories : Navigating Work and a Sense of Security - Scillio, Mark (Springer International Publishing : Imprint: Palgrave Macmillan, 2017)
This book is about how people construct career stories: the stories we use to make sense of our work life. Mark Scillio explores the idea of security in the current turbulent employment climate, investigating employment experiences in developed, wealthy countries like Australia, the United States, and the United Kingdom-where careers have become fragmented, complex, and uncertain. Using Anthony Giddens' notion of ontological security, Scillio develops a concept of career security that goes beyond economic and financial concerns and encompasses the personal and social meaning of work. The ramifications of succeeding (or failing) to forge a good career narrative are explored through a series of detailed case studies.